2020
DOI: 10.33263/briac103.466471
|View full text |Cite
|
Sign up to set email alerts
|

Acid – treated activated carbon for phenolic compound removal in acid pre-treatment of lignocellulosic biomass for biogas production

Abstract: Phenolic compound can be an inhibitor during acid pre-treatment process in the conversion of biomass into bioenergy and consequently reduces the production yield. Thus, this study aimed to investigate the potential use of activated carbon from coconut shell for phenolic compound removal and gallic acid was used as model phenolic. Granular activated carbon was treated by using 20% concentration of phosphoric acid to its properties and function. Acid treated and untreated activated carbon were characterized in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Similar results were obtained in the experiment conducted by Lee et al [ 26 ], in which the lower dosage of food waste-based biochar adsorbed the highest amount of phenol. Hamzah et al [ 79 ] explained that increasing the dosage after reaching the adsorptive optimum level could lead to adsorbent accumulation itself and overlaying the active site resulting in decreased removal efficiency. As for the adsorption dynamics experiment and the online solid phase extraction, OLP was the poorest adsorbed compound, albeit with the highest recovery, followed by GA and CA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained in the experiment conducted by Lee et al [ 26 ], in which the lower dosage of food waste-based biochar adsorbed the highest amount of phenol. Hamzah et al [ 79 ] explained that increasing the dosage after reaching the adsorptive optimum level could lead to adsorbent accumulation itself and overlaying the active site resulting in decreased removal efficiency. As for the adsorption dynamics experiment and the online solid phase extraction, OLP was the poorest adsorbed compound, albeit with the highest recovery, followed by GA and CA.…”
Section: Discussionmentioning
confidence: 99%
“…The adsorption capacity of CA on Active Charcoal TE80 ® (AC) was 229 mg kg −1 AC, which is almost 40-fold higher in comparison with the results obtained in this work. Furthermore, in another research [ 79 ], coconut shell-based activated carbon was used to determine its adsorption potential in phenolic compound removal using GA as a phenolic representative. The authors observed a few parameters that influenced the removal of GA; adsorbent dosage, initial concentration, contact time, and pH, concluding that the acid-treated activated carbon had successfully removed 97% of GA under specific conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the adsorption value after regeneration was 39.8÷7.2 mg‧ g -1 for adsorbent 0.5B-TiO2 at a confidence level of 95%. The test results indicate the suitability of Boron-dopped titanium dioxide in the acid medium and its ability for regeneration [26].…”
Section: Regeneration Of the Adsorbentsmentioning
confidence: 90%